Quality of Internet Videos Related to Pediatric Urology in Mainland China: A Cross-Sectional Study - Bai, Gaochen; Fu, Kai; Fu, Wen; Liu, Guochang (Frontiers in Public Health, 2022)
Background: Pediatric urological diseases pose serious threats to children's physical and mental health. The COVID-19 pandemic has resulted in poor pediatric outcomes for cryptorchidism, hypospadias, and testicular torsion. Presently, many people tend to seek health information via social media platforms. This study aims to quantitatively assess the quality of videos as an information source for pediatric urology in mainland China. Methods: In this cross-sectional study, a search was performed on social media platforms (Tiktok, Bilibili, and Weibo) with the search terms "cryptorchidism", "hypospadias", and "testicular torsion". The first 30 results with any search term listed by relevance were selected in each platform. Video features (duration, number of likes, comments, and shares) and video sources were collected. Each video included in the study was assessed using DISCERN, Journal of the American Medical Association (JAMA) Benchmark Criteria, and Hexagonal Radar Schema. A correlation analysis was performed considering video features, video source, DISCERN scores and JAMA scores. Results: A total of 152 videos were included and analyzed. The majority of videos were from physicians (65.8%). According to the DISCERN classification, most videos were rated as "very poor" (48.0%) and "poor" (36.8%). The mean DISCERN and JAMA scores were 36.56 and 2.68, respectively. The duration of videos uploaded by physicians was the shortest (P<0.001). The video source had no relevance to numbers of "likes", "comments", "shares", DISCERN scores, and JAMA scores (all P values>0.05). Other than video duration (P<0.001), there was no statistically significant difference between groups for any of the recorded or calculated video data (all P values>0.05). Hexagonal Radar Charts showed the severe imbalance and deficiency of video information. In general, Tiktok videos with the shortest duration received the most numbers of "likes", "comments", and "shares", whereas the overall quality of videos on Weibo was relatively high. Conclusions: Despite most of the videos on social media platforms being uploaded by medical authors, the overall quality was poor. The misleading, inaccurate and incomplete information may pose a health risk to the viewers, especially during the COVID-19 pandemic. Much effort needs to be undertaken to improve the quality of health-related videos regarding pediatric urology.